CLUSTER ANALYSIS EVALUATION ON GOVERNMENT PERFORMANCE WEST JAVA REGION USING DISSIMILARITY MEASURE - SUGILAR (NIM: 20107081), AGUS
The thesis analyzes survey result data of a non-government organization, REKODE, that is availabe at supervisor. Data is analyzed using single linkage cluster analysis with dissimilarity measure. For the first step, descriptive statistic in done. To make single linkage cluster analysis is implementable, each value of object (in this case is district/city) is represented by the value that appears more than 50% of all appearing values. One of the result that should the concern of many multicipalities is that some districts failed to decrease unemployment and corruption indices, especially Bekasi, Depok, Purwakarta and Sukabumi.